Bacterial diversity on larval and female Mansonia spp. from different localities of Porto Velho, Rondonia, Brazil - Oliveira, Tatiane M.P.; Rojas, Martha V.R.; Amorim, Jandui A.; Alonso, Diego P. [UNESP]; de Carvalho, Dario P.; Ribeiro, Kaio Augusto N.; Mureb Sallum, Maria Anice (Public Library of Science (PLoS), 2023)
Studies based on the bacterial diversity present in Mansonia spp. are limited; therefore, the aim of this study was to investigate the bacterial diversity in females and larvae of Mansonia spp., describe the differences between the groups identified, and compare the microbiota of larvae from different collection sites. Sequences of the 16S rRNA region from the larvae and females of Mansonia spp. were analyzed. Diversity analyzes were performed to verify the possible bacterial differences between the groups and the collection sites. The results showed Pseudomonas was the most abundant genus in both females and larvae, followed by Wolbachia in females and Rikenellaceae and Desulfovibrio in larvae. Desulfovibrio and Sulfurospirillum, sulfate- and sulfur-reducing bacteria, respectively, were abundant on the larvae. Aminomonas, an amino acid-degrading bacterium, was found only in larvae, whereas Rickettsia was identified in females. Bacterial diversity was observed between females and larvae of Mansonia and between larvae from different collection sites. In addition, the results suggest that the environment influenced bacterial diversity.